Relationship between high-fat diet, gut microbiota, and precocious puberty: mechanisms and implications - Wu, Nan; Ning, Ke; Liu, Yanan; Wang, Qinghua; Li, Ning; Zhang, Lei (Frontiers in Microbiology, 2025)
Precocious puberty (PP) is the second most common pediatric endocrine disorder globally and poses a growing public health concern, particularly among girls. While the exact biological mechanisms underlying PP remain unclear, unhealthy dietary patterns, particularly the consumption of a high-fat diet (HFD), are recognized as significant modifiable risk factors. The gut microbiota (GM) is an environmental factor that is disrupted by HFD and may modulate the onset and progression of PP. This review explored the intricate relationship between HFD, GM, and PP, and elucidated the potential mechanisms by which HFD may promote PP development by summarizing evidence from preclinical to clinical research, focusing on the role of GM and its derived metabolites, including short-chain fatty acids, bile acids, lipopolysaccharides, and neurotransmitters. Mechanistic exploration provides novel insights for developing microbiota-targeted therapeutic strategies, such as dietary and lifestyle interventions, fecal microbiota transplantation, probiotics, and traditional Chinese medicine, paving the way for promising approaches to prevent and manage PP.